The Populist Dynamic: Experimental Evidence on the Effects of Countering Populism - Vincenzo Galasso; Massimo Morelli; Tommaso Nannicini; Piero Stanig (Institute of Labor Economics (IZA), 2024)
We evaluate how traditional parties may respond to populist parties on issues aligning with populist messages. During the 2020 Italian referendum on the reduction of members of Parliament, we conducted a large-scale field experiment, exposing 200 municipalities to nearly a million impressions of programmatic advertisement. Our treatments comprised two video ads against the reform: one debunking populist rhetoric and another attributing blame to populist politicians. This anti-populist campaign proved effective through demobilization, as it reduced both turnout and the votes in favor of the reform. Notably, the effects were more pronounced in municipalities with lower rates of college graduates, higher unemployment, and a history of populist votes. This exogenous influence introduced a unique populist dynamic, observable in the 2022 national election where treated municipalities showed increased support for Brothers of Italy, a rising populist party, and decreased support for both traditional parties and the populists behind the 2020 reform. A follow-up survey further showed increased political interest and diminished trust in political institutions among the residents of municipalities targeted by the campaign.
Keywords: D72; C93; 330; voting; populism; randomized controlled trial